Women position in Abrahamic religions: A comparative study on the concept and philosophy of modesty and modest dress observance / Zohreh Sadatmoosavi - Zohreh, Sadatmoosavi (2016)
Today, women’s position in Abrahamic religions is a controversial issue in academia and media. Although there are many similarities among Abrahamic faiths, different interpretations about the creation and role of women are seen in their holy books and traditions. Abrahamic faiths have emphasized on observing modest behaviours for men and women and in this context have recommended women to wear modest dress. The common reasons in these faiths for head covering are piety, obedience of God, obtaining to Modesty virtue and protecting women’s immunity that lead toward illegal sex relations in society and protect the stability of the family as sacred scheme. The finding of this study demonstrates that despite of these similarities, some certain reasons in the Judeo-Christian teachings tradition are not applicable in Islam. This research is based on qualitative method that has an inductive approach.